Evaluation of a rapid combination disc test (RCDT) for direct phenotypic detection of extended-spectrum β-lactamase production in E. coli from positive blood culture bottles. (6th March 2023) - Berinson, Benjamin; Degel-Brossmann, Nicole; Olearo, Flaminia; Roggenkamp, Hannes G; Both, Anna; Aepfelbacher, Martin; Christner, Martin; Rohde, Holger
Abstract: Background: The spread of multi-resistant bacteria endangers the effectiveness of empirical antimicrobial treatment, particularly in Gram-negative bloodstream infections. Thus, rapid and reliable susceptibility testing has become a key challenge of modern microbiology. Here, we evaluated a combination disc test for rapid detection of ESBL production in Escherichia coli (rapid combination disc test, RCDT) directly from blood cultures. Methods: RCDT with discs containing cefotaxime and ceftazidime alone or in combination with clavulanic acid was validated using a cryo-collection of 96 third-generation cephalosporin-resistant (3GCR), whole-genome sequenced E. coli isolates spiked into blood culture bottles. All isolates were subjected to RCDT and rapid antibiotic susceptibility testing (RAST). Zone diameters were assessed after 4, 6 and 8 h of incubation. All isolates also underwent conventional combination disc testing. The real-life performance of RCDT was assessed by analysis of 306 blood cultures growing E. coli . Results: Eighty of 90 (88.9%) ESBL-positive E. coli validation isolates were correctly identified by RCDT after 4 h of incubation. The detection rate increased to 100% after 6 and 8 h. RCDT was negative in six 3GCR E. coli isolates expressing class B or C β-lactamases. RCDT from routine blood cultures correctly classified all 56 ESBL producers and 245/250 ESBL-negative isolates after 4 h, resulting in 100% sensitivity and 98.8% specificity. Conclusions: RCDT is a reliable method for rapid ESBL detection in E. coli directly from positive blood cultures. RCDT might complement RAST to support antibiotic stewardship interventions and treatment decisions.